Antisocial personality and aggressive behaviour intention among secondary school children in Malaysia - Duru, Chidiebere Kelechi (2015)
Although there is a literature related to children aggressive behaviour and its effects on adjustment and self-development, relatively little attention has been paid to the relationship between the factors that contributes to the explanation of aggressive behaviour. In line with this, the study examined the relationship between peer attachment, teacher attachment, antisocial personality, attitude to aggressive behavior, subjective norms to aggressive behaviors, perceived behavioural control and intention of aggressive behaviour. In addition, the study examined the mediating effect of subjective norms to aggressive behaviors, perceived behavioural control on the relationship between antisocial personality and aggressive behaviour among secondary school children in Selangor state, Malaysia. In this study, data was collected from 426 respondents, and a multistage random sampling techniques was applied to select the respondents from six secondary schools in four districts in Selangor, Malaysia. Data was collected using structured questionnaires. The descriptive analysis, paired sample t-test, Pearson correlation, multiple linear regression and Sobel mediation test were analyzed using SPSS version 20. The results of this study shown that, there is moderate level of peer attachment,teacher attachment, antisocial personality, attitude towards aggressive behavior, subjective norms to aggressive behaviors, perceived behavioural control, and aggressive behavior among secondary school children studied. Similarly, the result from paired sample t-test shows no significant difference in aggressive behaviour by gender, location, parental status, and age. However, there is significance difference in aggressive behaviour based on race. The result from Pearson correlation indicates that, there is a significant positive correlation between peer attachment and aggressive behavior; and a significant positive correlation between antisocial personality and aggressive behaviour. There is also a significant positive correlation between attitude to aggressive behaviour and aggressive behaviour. There is also a significant positive correlation between subjective norms to aggressive behaviour and aggressive behaviour. However, the analysis shows that, there is a significant negative correlation between teacher attachment, perceived behavioural control and aggressive behaviour; Furthermore, the results of the multiple linear regression analysis as a whole (which includes peer attachment, teacher attachment, antisocial personality, attitude to aggressive behavior, subjective norms to aggressive behavior and perceived behavioral control) is significant (F (6,419) = 18.267, p = .000). This indicated that the slope of the estimated linear regression model line is not equal to zero. The result generated by the SPSS showed that, about 20.7% variance in aggressive behaviour was explained by the all the predictor variables entered into the regression model. The analysis shows that, the four independent variables were significantly contributed to aggressive behaviour. The Sobel mediation test furthermore indicates that subjective norms to aggressive behaviour, perceived behavioural control mediates the relationship between antisocial personality and aggressive behaviour. Based on this result, the researcher concluded that, environment, peers socialization and influence in the school has leads to the real aggressive behaviour among secondary school children in Selangor,Malaysia. This study is in line with the previous literature by indicating that, school environment, influence of peers and socialization has the highest significant contribution to children aggressive behaviour. Moreover, some recommendations are forwarded to help secondary schools and families keep their environment free of aggressive behaviour.